Feedforward Current References Control for DFIG-Based Wind Turbine to Improve Transient Control Performance During Grid Faults - Zhu, Donghai; Zou, Xudong; Zhou, Shiying; Dong, Wen; Kang, Yong; Hu, Jiabing (IEEE transactions on energy conversion, 2018)
For doubly fed induction generator (DFIG) based wind turbines, when severe grid faults occur, it is necessary to inject transient and negative-sequence components into the rotor current reference to achieve controllable low-voltage ride through (LVRT) capability. However, the classical proportional-integral (PI) controller cannot provide precise control of the transient and negative-sequence rotor current, because such current references in synchronous reference frame (SRF) are ac components at grid frequency and double grid frequency, respectively. To solve this problem, this paper proposes a feedforward current references control (FCRC) method for rotor-side converter to improve the system transient control performance. Under the proposed method, the additional feedforward of rotor current references is introduced into the current loop to improve its tracking capability of the aforementioned ac current references, thereby achieving the transient control targets precisely. Moreover, the proposed method will not affect the stability of the original current loop. Furthermore, the method has strong robustness against DFIG parameters deviation and grid frequency variations. In addition, the method is highly simple to implement. Finally, the validity of the proposed FCRC method is demonstrated by simulation and experiment.